Deep XMM-Newton observations of the northern disc of M31. II. Tracing the hot interstellar medium - Kavanagh, Patrick J.; Sasaki, Manami; Breitschwerdt, Dieter; de Avillez, Miguel A.; Filipović, Miroslav D.; Galvin, Timothy; Haberl, Frank; Hatzidimitriou, Despina; Henze, Martin; Plucinsky, Paul P.; Saeedi, Sara; Sokolovsky, Kirill V.; et al. (2020)
Aims: We use new deep XMM-Newton observations of the northern disc of M31 to trace the hot interstellar medium (ISM) in unprecedented detail and to characterise the physical properties of the X-ray emitting plasmas. Methods: We used all XMM-Newton data up to and including our new observations to produce the most detailed image yet of the hot ISM plasma in a grand design spiral galaxy such as our own. We compared the X-ray morphology to multi-wavelength studies in the literature to set it in the context of the multi-phase ISM. We performed spectral analyses on the extended emission using our new observations as they offer sufficient depth and count statistics to constrain the plasma properties. Data from the Panchromatic Hubble Andromeda Treasury were used to estimate the energy injected by massive stars and their supernovae. We compared these results to the hot gas properties. Results: The brightest emission regions were found to be correlated with populations of massive stars, notably in the 10 kpc star-forming ring. The plasma temperatures in the ring regions are ~0.2 up to ~0.6 keV. We suggest this emission is hot ISM heated in massive stellar clusters and superbubbles. We derived X-ray luminosities, densities, and pressures for the gas in each region. We also found large extended emission filling low density gaps in the dust morphology of the northern disc, notably between the 5 and 10 kpc star-forming rings. We propose that the hot gas was heated and expelled into the gaps by the populations of massive stars in the rings. Conclusions: It is clear that the massive stellar populations are responsible for heating the ISM to X-ray emitting temperatures, filling their surroundings, and possibly driving the hot gas into the low density regions. Overall, the morphology and spectra of the hot gas in the northern disc of M31 is similar to other galaxy discs. FITS files for Figs. 1 and 2 are only available at the CDS via anonymous ftp to http://cdsarc.u-strasbg.fr (ftp://130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/cat/J/A+A/637/A12 Based on observations obtained with XMM-Newton, an ESA science mission with instruments and contributions directly funded by ESA Member States and NASA.
Keywords: galaxies: ISM; HII regions; ISM: bubbles; ISM: structure; X-rays: ISM